Effect of cement – aggregate ratio with an alkaline addition (NaOH) on the mechanical properties of compressed stabilised earth cubes - Muhammad Syahredzuan, Rusli (2015)
ustrialized Building System (IBS). The usage of CSEB in development industry can be new construction material which is more efficient that can save overall construction period and cost. Nowadays, CSEB are one of the first choices as building materials that being used in the construction. There are so many factors that need to be considered in making stronger compressed stabilised earth cubes especially in term of its strength and durability that to be applied in building construction. The presence of an alkaline solution, optimum mix proportion (cement, soil and sand) and curing method will affect the cubes strength. The purposes for this research are to determine the compressive strength, abrasion and water absorption of the cubes by using different proportion ratios of aggregates added to the cement and also to determine the effect of alkaline to the compressive strength of the cubes. Three sets of cube which are constant in cement-aggregates ratio, 1:8 but different in soil-sand ratio (1:2:6, 1:3:5 and 1:4:4) were carried out. Each set will include an alkaline solution in different concentration which are 1, 2 and 3molarity. The only curing method used is air curing for 28 days. Cubes mechanical properties can be determine by compression test, abrasion test and water absorption test. The highest compressive strength result achieved for control is in 1:4:4 mix proportion with a value of 4.599MPa for 28 days curing age and for the presence of an alkaline solution the highest strength is in 1:4:4 mix proportion with 1mol of concentration, 4.555MPa. All cubes strength did not achieved 5.2MPa at 28 days aged of curing to satisfy the minimum permissible average compressive strength for the cubes. Water absorption for 1:3:5 cubes mix proportion shows lowest percentage compare to the others. The cubes also have their own durability and would be able withstand in harsh environment since the average percentage losses are very small which is less than 1.5%